Effect of Different Organic And Inorganic Fertilizers on the Growth and Yield of Wetland Rice (International Journal of Natural Sciences, 2016)
Two experiments were conducted at farmers field of Tukerbazer, Sylhet in Boro season and T. aman season of 2013 in order to test the effect of different organic and inorganic fertilizers on the growth and yield of wetland rice. Eight treatment combinations were tested in T. aman season namely T1= Control (without fertilizer), T2= Agro-Sar (Organo-Chemical) (ASOC) @ 750 kg/ha, T3= STB (Soil Test Based), T4= T2+50% STB, T5= T2 + 60% STB, T6= T2 + 70% STB, T7= T2 + 80% STB and T8= T2 + T3 where BRRI dhan31 was used as test crop. In Boro season, the following ten treatment combinations were tested in Boro season: namely T1= FRG 05 dose: N, P, K, S and Zn @ 123, 26, 60, 13 & 4 kg/ha, T2= Agro meal plus @ 300 kg/ha, T3= T2 + N, P, K, S @ 74, 16, 60 and 8 kg/ha, T4= ASO @ 740 kg/ha, T5= T4 + N, P, K, S @ 74, 16, 60 and 8 kg/ha, T6= Agro-Sar (Organo-chemical) (ASOC) @ 740 kg/ha, T7= T6 + N, P, K, S @ 74, 18, 36 and 8, T8= Raj Jaibo Sar @ 790 kg/ha, T9 = T8 + N, P, K, S @ 74, 20, 54 and 9 kg/ha, and T10= Control (without fertilizer). The blanket doses of fertilizers were applied as soil test based (STB). The experiments were laid out in Randomized Complete Block Design with 3 replications of each treatment. The sources of N, P, K & S were USG, TSP, MP and gypsum. The treatment T4 where USG was deep-placement produced the maximum yield and also found superior in terms of economic point of view.International Journal of Natural Sciences (2015), 5(2) 80-85